Implementation of Audio-Visual Media in Fiqh Learning Activities: Penerapan Media Audio-Visual dalam Kegiatan Pembelajaran Fiqh - Kholip, Nor; astutik, anita puji (Indonesian Journal of Education Methods Development, 2025)
General background: Learning media is a crucial component in modern education, serving as a bridge for knowledge transfer through audio, visual, and audiovisual formats. Specific background: In Islamic education, particularly in fiqh learning at elementary level, traditional teaching methods often limit students’ engagement and comprehension. Knowledge gap: Few studies have deeply explored how audiovisual media specifically supports cognitive, affective, and participatory aspects of fiqh learning in madrasah contexts. Aims: This study investigates the implementation of audiovisual learning media in Grade V fiqh lessons at MI Unggulan Miftahul Huda, focusing on challenges, benefits, and learning outcomes. Results: Findings indicate that audiovisual media improves students’ understanding of complex fiqh concepts, increases active participation, and stimulates motivation, although challenges remain in teacher expertise, time management, and facility availability. Novelty: The study highlights the integration of audiovisual media as a concrete approach aligned with students’ developmental stages, providing richer learning experiences than conventional methods. Implications: Proper utilization of audiovisual technology can strengthen Islamic education delivery, foster deeper comprehension, and contribute to sustainable quality improvement in religious learning. Highlights: Audiovisual media improves comprehension and engagement in fiqh learning. Teachers face challenges in technology mastery and resources. Novel integration aligns with students’ cognitive developmental stages. Keywords: Learning Media, Audiovisual, Fiqh Education, Islamic Education, Educational Technology